Espectrofotometría y colorimetría - Rojas Gutiérrez, Daniél César (2022)
The present work "Spectrophotometry and colorimetry", is a bibliographic review of all the aspects, concepts, and applications that the topic in question has in the food industry. Which is very important because the application of these, allows to optimize quality standard manufacturing processes in food production. Spectrophotometry and colorimetry are widely used methods of analysis, and are based on the relationship between the absorption of light by a compound and its concentration. Depending on the compound and the type of absorption to be measured, the sample can be in liquid, solid or gas phase. In the visible and ultraviolet regions of the electromagnetic spectrum, the sample is generally dissolved to form a solution. A key and indispensable factor in the growth of the food industry using colorimetry and spectrophotometry is the understanding and ease of adaptation to data software for color measurement, matching, formulation and quality control of color and food components. A food.